1993
DOI: 10.1148/radiology.188.1.8390071
|View full text |Cite
|
Sign up to set email alerts
|

Experimental liver cancers: Mn-DPDP-enhanced rims in MR-microangiographic-histologic correlation study.

Abstract: During both animal and clinical studies with manganese (II) N,N'-dipyridoxylethylenediamine-N,N'-diacetate 5,5'-bis(phosphate) (DPDP), enhanced rims around liver tumors on magnetic resonance (MR) images have been observed. To elucidate the origins of these rims and to assess their potential value in the differential diagnosis of liver masses, the authors studied 15 rats with induced hepatocellular carcinoma (HCC), 10 rats with implanted Novikoff hepatomas, and 11 rabbits with implanted VX2 carcinomas. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 0 publications
3
45
0
Order By: Relevance
“…However, because the rim-like enhancement on Mn-DPDPenhanced MR images, as often seen in HCC, is theoretically unlikely to appear in metastases of the colon, we believe that some mistake might have been made regarding the sampling or histopathologic diagnosis. The underlying mechanism for the occurrence of rim-like enhancement in some metastatic liver tumors has been attributed to several causes (26). First, peritumoral malignant infiltration into neighboring normal liver parenchyma can result in intermingling of nonhepatocellular malignant cells with normal functioning hepatocytes in the peripheral region of liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the rim-like enhancement on Mn-DPDPenhanced MR images, as often seen in HCC, is theoretically unlikely to appear in metastases of the colon, we believe that some mistake might have been made regarding the sampling or histopathologic diagnosis. The underlying mechanism for the occurrence of rim-like enhancement in some metastatic liver tumors has been attributed to several causes (26). First, peritumoral malignant infiltration into neighboring normal liver parenchyma can result in intermingling of nonhepatocellular malignant cells with normal functioning hepatocytes in the peripheral region of liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…First, peritumoral malignant infiltration into neighboring normal liver parenchyma can result in intermingling of nonhepatocellular malignant cells with normal functioning hepatocytes in the peripheral region of liver metastasis. Second, compression of surrounding normal liver tissue by a metastatic tumor mass may lead to impaired Mn-DPDP excretion or persistent Mn-DPDP retention because of the compressed bile canaliculi in these areas (26).…”
Section: Discussionmentioning
confidence: 99%
“…It was not until early 1990s that DENA-induced HCC lesions could have been noninvasively characterized by MRI in living rats, on which a methodology paper [6] was granted the Stauffer Award in 1993 by the Association of University Radiologists and Society of Chairs of Academic Radiology Departments [http://www.aur.org/Awards_Training_Grants/stauffer.cfm]. Since then, a research platform based on this model has played a major role in preclinical evaluations of a number of newly developed specific MRI CAs [6,[9][10][11][12][13][14][15] and contributed to the discovery of necrosis avid contrast agents (NACAs) for, among many other applications, determination of myocardial infarction and anticancer therapeutic assessment [16][17][18][19][20].…”
Section: Primary Liver Cancer Model In Ratsmentioning
confidence: 99%
“…Consequently, such a comprehensive modeling system allowed appreciation of the contributions of not only intra-and extra-vascular compartments [22] but also active cellular uptake to the final contrast enhancement (CE) patterns. The latter aspect proves particularly important in the studies on tissue specific MRI CAs [6,[9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Primary Liver Cancer Model In Ratsmentioning
confidence: 99%
“…In 1993, Ni et al (19), performing microangiographic and histologic correlations, reported that enhanced rims seen around liver tumors with manganese (II) N, NЈ-dipyridoxylethylenediamine-N, NЈ-diacetate 5,5Ј-bis (phosphate) (DPDP)-enhanced MR images corresponded to the peritumoral zones of malignant infiltration, surrounding parenchymal compression, and bile duct proliferation. Meanwhile, the usefulness for hepatic lesion characterization by identifying ring enhancement on conventional T1-weighted SE images following ultra-small superparamagnetic iron oxide compound with prolonged blood half-life was first described by Mergo et al (16).…”
Section: Discussionmentioning
confidence: 99%